Profiling gender differentials in asset and debt portfolios in Australia - Jefferson, Therese; Ong, Rachel (Centre for Research in Applied Economics, Curtin Business School, 2010)
This paper investigates gender differentials in asset and debt portfolios in Australia using the 2006 Household, Income and Labour Dynamics in Australia (HILDA) Survey. The explorations described in this paper indicate that there are gendered dimensions to both the value and composition of asset and debt holdings in Australia. If we compare couple households with single men and women households then we find that women have both lower asset holdings and portfolios that are relatively overweighted in the primary home. In some respects single men households have portfolios that more closely resemble those of couple households than single women’s portfolios. This is particularly the case with the lower proportion of single men’s portfolios held in their primary home and their holding of accumulated superannuation wealth. To the extent that data reveal insights into gendered patterns of intrahousehold asset holdings, women’s holdings of solely owned assets are lower then men’s in all age groups and across all types of assets for which data are available. This pattern is particularly evident in de facto opposite sex couple households.